2008
DOI: 10.1016/j.ijgo.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone therapy with estrogen and/or progesterone on sleep pattern in postmenopausal women

Abstract: While not significantly affecting sleep quality, hormone therapy decreased the prevalence of arousal in both groups and that of PLM in the group treated with estrogen plus progesterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 25 publications
2
55
1
6
Order By: Relevance
“…Combined estrogen-progesterone therapy attenuated breathing irregularities, periodic limb movements, nocturnal arousals, hot flashes and bruxism (teeth grinding) in a study involving 33 postmenopausal women [104]. In patients with central sleep apnea, progestins may alleviate hypoventilation by providing stimulatory drive to brainstem respiratory centers.…”
Section: Gonadal Hormones and Sleep Disordersmentioning
confidence: 99%
“…Combined estrogen-progesterone therapy attenuated breathing irregularities, periodic limb movements, nocturnal arousals, hot flashes and bruxism (teeth grinding) in a study involving 33 postmenopausal women [104]. In patients with central sleep apnea, progestins may alleviate hypoventilation by providing stimulatory drive to brainstem respiratory centers.…”
Section: Gonadal Hormones and Sleep Disordersmentioning
confidence: 99%
“…11 Estrogen therapy has been reported to reduce PLMs, 12 and a later study observed that estrogen in addition to progesterone was more effective than estrogen alone in decreasing the prevalence of PLMs. 13 RLS is approximately twice as common in women as men, and its prevalence increases following the onset of menopause.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…The principle of action of intraoral devices is to promote alterations in the anatomical structures of the upper airways to maintain the influence of these ways during the night breathing Regarding the pharmacological treatment specific to this syndrome, several studies involving different pharmacological groups has presented controversial results; there are still no clinical evidences about its effectiveness 34 . The speech therapy is considered a new treatment option to OSAHS and snoring, presenting satisfactory results and significant initial symptoms in life quality in a short time.…”
Section: Final Considerationsmentioning
confidence: 99%